2018
DOI: 10.5539/jas.v11n1p448
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Quality of Common Bean Seeds Subjected to Different Concentrations of Salicylic Acid

Abstract: Salicylic acid acts on several plant physiological processes. Therefore, the aim of this study was to determine if salicylic acid interferes on the physiological quality of common bean seeds soaked with different concentrations by testing two seed imbibition methodologies. Common bean seeds of the cultivars Fepagro 26 and Predileto were utilized. The seeds were soaked in solutions of salicylic acid with concentrations of zero, 250, 500, 750, 1,000, 3,000 and 5,000 μM. Seed imbibition occurred in two way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…The variables of first germination count (FGR) and germination (GER), at 5 and 9 DAS, respectively, gave similar results, with general averages of 95, 92, 77, 71 and 64% of FGR and GER for storage periods of 0, 3, 6, 9 and 12 months in cold chambers, in that order. Fernandes et al (2019) found that black bean seeds showed similar FGR and GER, even when subjected to saline conditions. (MAPA) (Brazil, 2013), black bean seeds must have at 70% germination for the basic commercial category and for other categories at least 80% germination.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The variables of first germination count (FGR) and germination (GER), at 5 and 9 DAS, respectively, gave similar results, with general averages of 95, 92, 77, 71 and 64% of FGR and GER for storage periods of 0, 3, 6, 9 and 12 months in cold chambers, in that order. Fernandes et al (2019) found that black bean seeds showed similar FGR and GER, even when subjected to saline conditions. (MAPA) (Brazil, 2013), black bean seeds must have at 70% germination for the basic commercial category and for other categories at least 80% germination.…”
Section: Resultsmentioning
confidence: 95%
“…The production of black beans (Phaseolus vulgaris L.) in Brazil is intended for domestic consumption, with family farming being responsible for a large part of this production. One of the fundamental agricultural inputs for productivity is good quality seeds, which guarantee sustainability and food security, both for this type of agriculture and for domestic consumption (Sousa and Wander, 2014;Fernandes et al, 2019).…”
mentioning
confidence: 99%
“…Resultados semelhantes ao do presente trabalho, foram observados por Fernandes et al (2019) em que as soluções com ácido salicílico acima de 500 µM resultaram em menor porcentagem de germinação de sementes de feijão (Phaseolus vulgaris L.).…”
Section: Resultsunclassified
“…Resultados semelhantes ao do presente trabalho, foram observados por Fernandes et al (2019) em que as soluções com ácido salicílico acima de 500 µM resultaram em menor porcentagem de germinação de sementes de feijão (Phaseolus vulgaris L.). Figura 1.…”
Section: Resultsunclassified